Prognostic value of serum lipids in newly diagnosed acute promyelocytic leukemia - Wang, Shijie; Wang, Qian; Lv, Shuxin; Qin, Ling (Frontiers in Oncology, 2025)
Background and purposeDyslipidemia has been linked to acute promyelocytic leukemia (APL), with abnormal lipid metabolism observed during treatment. However, its role in APL pathogenesis remains unclear. This study investigates the relationship between serum lipid levels and clinical features, risk stratification, bleeding tendency, and prognosis of newly diagnosed APL patients, focusing on the role of the PTK2 gene in regulating lipid metabolism and its potential as a therapeutic target.Materials and methodsWe analyzed 90 newly diagnosed APL patients and 99 controls. Statistical analyses, including logistic regression, survival analysis, and protein-protein interaction (PPI) network, were used to assess lipid correlations with APL. Subgroup analyses explored specific clinical impacts, and functional experiments validated PTK2’s role in lipid metabolism.ResultsElevated triglycerides (TG) were positively associated with high-risk APL, while reduced high-density lipoprotein cholesterol (HDL-C) levels correlated with lower risk. Low-density lipoprotein cholesterol (LDL-C) was an independent prognostic marker, with lower levels linked to poorer outcomes. PTK2 expression significantly promoted APL cell proliferation, migration, and lipid metabolism, highlighting its role in APL pathogenesis. PTK2 regulates lipid metabolism-related factors, such as LDL and fibrinogen, through molecular pathways.ConclusionDyslipidemia is closely related to APL, with TG and LDL-C levels being key prognostic indicators. PTK2 plays a crucial role in lipid metabolism regulation and APL progression, providing a new molecular basis for risk assessment and targeted therapy. These findings offer potential biomarkers for early diagnosis and personalized treatment strategies.